THE ECONOMIC AND SOCIAL RATIONALE FOR INCREASING HOUSEHOLD INCOMES THROUGH THE DEVELOPMENT OF THE TOURISM SECTOR - Ravshanova Muhayyo Makhmanazarovna; Jo‘rayev G‘ayrat Shog‘darovich (Bright Mind Publishing, 2025)
This article analyzes the issue of increasing household incomes through the development of the tourism sector. Tourism is an important factor in economic growth and has a positive impact on public welfare as a direct and indirect source of income. The article highlights the potential to boost the sector by efficiently utilizing Uzbekistan’s existing tourism resources, developing tourism infrastructure, improving service quality, and implementing digital technologies. Additionally, it substantiates the social and economic significance of tourism through the creation of new jobs and the engagement of local communities in entrepreneurship. The research findings reveal ways to support the national economy through the comprehensive development of tourism.
Keywords: Tourism, household income, economic development, tourism infrastructure, domestic and international tourism, service sector, digital technologies, employment, cultural heritage, sectors of the economy.